Faktor-Faktor Pertumbuhan Ekonomi Pada Sektor Yang Ada Di Kota Batam - Novia, Jessica; Haryanto, Hery; Huang, Chyntia; Willyanto, Lia; Sisca, Veni (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Batam's economic growth has decreased in recent years. As one of the Free Trade Zone (FTZ) areas that are very possible to attract investors from abroad to make Foreign Investments (PMA), Batam City should have great economic growth. With this, it encourages the author to conduct research in order to determine the factors causing the decline in economic growth in Batam City. Where to obtain information, we use descriptive quantitative methods. The information obtained can be seen that Foreign Investment (PMA) greatly affects the economic growth rate of Batam City. The decline in PMA, the Gross Regional Domestic Product (PDRB) also decreased. So that it can be one of the determining factors for the size of the UMR in Batam City. The decline in PMA is due to the COVID-19 pandemic situation and overlapping regulations between the two agencies, namely BP Batam and Pemko Batam. Therefore, the author would like to recommend in order to clarify the law (regulation) between BP Batam and Pemko Batam. So as not to cause inconvenience to investors due to overlapping regulations.